“we can all meet, be it soon or late”: E. A. Petherick and his scholarly and publishing social network - Rukavina, Alison (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2012)
Between 1870 and 1895, Australian bookseller Edward Petherick was an active member of the Royal Geographical Society, Hakluyt Society, and other groups interested in colonial trade and history, as well as increasingly an important figure in the developing international book trade. His surviving correspondence is the physical remnants of his social network and the many connections and exchanges he facilitated, including the sale and distribution of the explorer Richard F. Burton’s Arabian Nights in the colonies. Petherick considered it a privilege to engage with his correspondents and help individuals because knowledge did not flow in one direction in a social network. As Petherick assisted others who wanted to sell books overseas and learn about the colonies, he also benefited and gained knowledge that furthered his own interests and scholarly work.